Gene Therapy with HSV1-sr39TK/GCV Exhibits a Stronger Therapeutic Efficacy Than HSV1-TK/GCV in Rat C6 Glioma Cells - Li, Lei-qing (Hindawi Publishing Corporation, 2013)
Although the combination of herpes simplex virus type 1 (HSV-1) thymidine kinase (TK) with ganciclovir (GCV) has been shown as a promising suicide gene treatment strategy for glioma, the almost immunodepressive dose of GCV required for its adequate in vivo efficacy has hampered its further clinical application. Therefore, In order to reduce the GCV dose required, we aim to compare the therapeutic efficacy of HSV1-sr39TK, an HSV1-TK mutant with increased GCV prodrug catalytic activity, with wildtype TK in C6 glioma cells. Accordingly, rat C6 glioma cells were first transfected with pCDNA-TK and pCDNA-sr39TK, respectively, and the gene transfection efficacy was verified by immunocytochemistry and western blot analysis. Then the in vivo sensitivity of these transfected C6-TK and C6-sr39TK cells to GCV was determined by 3-(4,5)-dimethylthiahiazo-(-z-y1)-3,5-di-phenytetrazoliumromide (MTT) colorimetric assay and Hoechst-propidium iodide (PI) staining. Finally, a subcutaneously C6 xenograft tumor model was established in the nude mice to test the in vitro efficacy of TK/GCV gene therapy. Our results showed that, as compared with wildtype TK, HSV1-sr39TK/GCV demonstrated a stronger therapeutic efficacy against C6 glioma both in vitro and in vivo, which, by reducing the required GCV dose, might warrant its future use in the treatment of glioma under clinical setting.